2000
DOI: 10.1021/jf990408j
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Characterization of Enzymes Causing Starch Degradation in Rice (Oryza sativa Cv. Koshihikari)

Abstract: The thermal dependency and stability of enzymes producing reducing sugar (RS) were examined in bran, the exterior 13% part (outer endosperm), and the remaining inner endosperm of rice grains. RS-producing enzymes in the inner endosperm showed a higher optimum temperature than those in other parts of the rice grain. Diethylaminoethyl-Sephacel chromatography of crude extracts revealed two peaks of RS-producing activity with different optimum temperatures (60 and 37 degrees C) in all three parts. alpha-Glucosidas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 35 publications
4
24
0
2
Order By: Relevance
“…14) Iwata has reported that the -glucosidase activity showed a positive correlation with the GBSS activity and amylose content. 15) This can be explained by a relationship between -glucosidase and starch accumulation in developing rice.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…14) Iwata has reported that the -glucosidase activity showed a positive correlation with the GBSS activity and amylose content. 15) This can be explained by a relationship between -glucosidase and starch accumulation in developing rice.…”
Section: )mentioning
confidence: 99%
“…14,15) The -glucosidase genes have been identified by Nakai et al during the ripening and germinating stages in rice. 18) We designed primers a (5 0 -ggt aca acg tcg cgt cgg-3 0 , sense) by using from number 128 nucleotide to number 146 nucleotide, and primer b (5 0 -gcc gcc gcc gga gcg cac-3 0 , antisense) by using from number 687 nucleotide to number 705 nucleotide of identified -glucosidase reported by Nakai et al (Fig.…”
Section: Development Of Sts Primers For Pcrmentioning
confidence: 99%
“…Nakai et al also demonstrated that ONG2-II is the major isoform in dormant rice and is a post-translational isoform of ONG2-I. The existence of an ONG2-II-like α-glucosidase is implicated in Koshihikari (Awazuhara et al, 2000;Mabashi et al, 2009) and Yamadanishiki (Iwata et al, 2003). the mixtures for 15 h at 4℃.…”
Section: Introductionmentioning
confidence: 97%
“…The transferred membrane was incubated in 20 mM Tris buffered saline (TBS, pH 7.5) containing 0.1% Tween-20 and 5% skim milk for blocking. The transferred membrane was reEnzyme assays in the dormant rice revealed the distribution of enzyme activity: α-glucosidases in the inner endosperm, α-amylases in the outer layers, and β-amylases in whole grains (Awazuhara et al, 2000;Iwata et al, 2002). However, the particular distribution of each enzyme isoform in dormant grains is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Nakai et al also demonstrated that ONG2-II is the major isoform in dormant rice and is a post-translational isoform of ONG2-I. The existence of an ONG2-II-like α-glucosidase is implicated in Koshihikari (Awazuhara et al, 2000;Mabashi et al, 2009) and Yamadanishiki (Iwata et al, 2003). Isoamylases and pullulanase are enzymes that hydrolyze the α-1,6-glucosidic linkage of amylopectin.…”
Section: Introductionmentioning
confidence: 99%